An Incremental OCL Compiler for Modeling Environments - Vajk, Tamas; Mezei, Gergely; Levendovszky, Tihamer (Electronic Communications of the EASST, 2008)
In software engineering, reliability and development time are two of the most important aspects, therefore, modeling environments, which aide both, are widely used during software development. UML and OCL became industry standards, and are supported by many CASE tools. OCL code checking, which has to be performed by these tools, has a specialty, as not all of the information necessary for compilation is available from the code, the related model contains the types, navigations and attributes. The build time of OCL code fragments is increased if the development tool supports distributed modeling, because in this case, model element checking has to be performed in a model repository that cannot be held in memory. In this paper, we introduce a method that enables incremental OCL code building and therefore reduces the development time. Incremental builds require higher complexity than simple builds, thus balancing between the two methods is also considered.